The nest architecture of Euglossa (Euglossa) hemichlora (Hymenoptera: Apidae: Euglossini) - PARRA-H., ALEJANDRO; NATES-PARRA, GUIOMAR (Revista Colombiana de Entomología, 2009)
Information on the nesting biology of orchid bees is scarce due to the great difficulty of finding their nests. Comments and observations are presented about the architecture of the nests of Euglossa hemichlora obtained from trap nests as well as data on the nesting biology of this species of orchid bee.